2015
DOI: 10.1111/rda.12562
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Canine Induced Pluripotent Stem Cells

Abstract: Dogs and humans have many inherited genetic diseases in common and conditions that are increasingly prevalent in humans also occur naturally in dogs. The use of dogs for the experimental and clinical testing of stem cell and regenerative medicine products would benefit canine health and welfare and provide relevant animal models for the translation of therapies to the human field. Induced pluripotent stem cells (iPSCs) have the capacity to turn into all cells of the body and therefore have the potential to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 37 publications
3
60
0
2
Order By: Relevance
“…In the current report, we established stable and long‐term cultures of ciPSCs using a doxycycline‐inducible system. ciPSCs had not been previously maintained long‐term (Baird et al, ; Gonçalves et al, ; Luo et al, ), and even canine embryonic stem cells could be cultured for a maximum of 40 passages (Hatoya et al, ; Hayes et al, ; Schneider, Wolf, Braun, Kolb, & Adler, ; Vaags et al, ; Wilcox et al, ). Whitworth et al () reported that ciPSCs could be passaged over 40 times, but their lines did not form a teratoma after transplantation into an immunodeficient mouse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current report, we established stable and long‐term cultures of ciPSCs using a doxycycline‐inducible system. ciPSCs had not been previously maintained long‐term (Baird et al, ; Gonçalves et al, ; Luo et al, ), and even canine embryonic stem cells could be cultured for a maximum of 40 passages (Hatoya et al, ; Hayes et al, ; Schneider, Wolf, Braun, Kolb, & Adler, ; Vaags et al, ; Wilcox et al, ). Whitworth et al () reported that ciPSCs could be passaged over 40 times, but their lines did not form a teratoma after transplantation into an immunodeficient mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, derived ciPSCs cultured in medium supplemented with bFGF and LIF formed complete teratoma that also possessed up‐regulated transgene expression (Koh et al, ; Vaags et al, ), implying that teratoma formation requires transgene expression as well as active bFGF and LIF signaling in ciPSCs; perhaps our ciPSCs may have formed teratomas if they were cultured with bFGF plus LIF and if doxycycline was administered to the mice to maintain the expression of transgenes after transplantation. Several groups reported that the expression of transgenes is maintained in ciPSCs (Baird et al, ; Gonçalves et al, ; Luo et al, ; Nishimura et al, ). Conversely, Whitworth et al () reported that transgene expression in their ciPSCs was completely silenced, suggesting that the long‐term maintenance of their ciPSCs without exogenous expression might be attributed to achievement of reprogramming at the same level as that of canine embryonic stem cells using mitogen‐activated protein kinase inhibitor and glycogen synthase kinase 3β inhibitor (Baird et al, ; Gonçalves et al, ; Luo et al, ; Nishimura et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В 2015 г. нами получены ИПСК американской норки, и, таким образом, появилась уни-кальная возможность сравнения полученных из эмбриона и индуцированных плюрипотентных клеток на новом, сравнительно мало исследованном виде (Menzorov et al, 2015). Ключевые транскрипционные факторы, по-зволяющие индуцировать плюрипотентность в геноме дифференцированных клеток, достаточно консервативны, что позволяет использовать для репрограммирования диф-ференцированных клеток различных видов гены человека, например для получения ИПСК собаки (Baird et al, 2015). Так, представленная система репрограммирования генома с минимальными модификациями была успешно при-менена нами для получения ИПСК как человека и мыши (неопубл.…”
unclassified